(3SdhGf GdeWGY aj YOhGf GdEJHGYs - (3MLI GdOjf GdUbdj , eMeO Hf CHj eMeO Hf XaQ, CHh YHO Gddg,J (B550 (3g` s
(3ChdgG (B:s
(3bGd YHO Gddg GdabjQ Edi QMeJg Ef MeO Gddg dCSfi GdedGHS GdaGNQI hGdMeO ddg GdPi Ndb GdHQjI GdCOejI aCMSf NdbgG s
(3BNQgG (B:s
(3Ke Efi CNWH Edi ef HdZg cdGei efShH Edi JYjf gahGJ GddSGf hgHg GdGSGg ddEMSGf Je GdSdhGf hHGddg GdeSJYGf hMSHfG dGdg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3HChdg Jedcs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B205s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs